2016
DOI: 10.1039/c5fo00892a
|View full text |Cite
|
Sign up to set email alerts
|

Acutely administered grape-seed proanthocyanidin extract acts as a satiating agent

Abstract: Grape-seed proanthocyanidins' role as stimulators of active GLP-1 in rats suggests that they could be effective as satiating agents. Wistar rats were used to study the effects of proanthocyanidins on food intake with different doses, administration times and proanthocyanidin extract compositions. A dose of 423 mg of phenolics per kg body weight (BW) of grape-seed proanthocyanidin extract (GSPE) was necessary to decrease the 12-hour cumulative food intake by 18.7 ± 3.4%. Proanthocyanidins were effective when de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
58
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 50 publications
(63 citation statements)
references
References 48 publications
5
58
0
Order By: Relevance
“…Given that GSPE was effective in increasing active GLP-1 levels [36] at doses inhibiting food intake [17], we checked the role of GLP-1 in this effect on food intake. Figure 3a shows that the short-term effects of GSPE on food intake were antagonized by the GLP-1 receptor (GLP-1-R) antagonist Ex9 [29], as was the case with i.p.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Given that GSPE was effective in increasing active GLP-1 levels [36] at doses inhibiting food intake [17], we checked the role of GLP-1 in this effect on food intake. Figure 3a shows that the short-term effects of GSPE on food intake were antagonized by the GLP-1 receptor (GLP-1-R) antagonist Ex9 [29], as was the case with i.p.…”
Section: Resultsmentioning
confidence: 99%
“…We initially defined the inhibitory effect of GSPE on food intake in female, male, young, aged, normofagic and hyperfagic animals after an acute treatment [17]. Afterwards, we showed that a specific dose is needed to ensure a significant chronic effect on body weight control [14].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations